2007
DOI: 10.1158/1078-0432.ccr-06-2762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytarabine and Decitabine in Combination in Human Leukemic Cell Lines

Abstract: Purpose: 1-h-D-Arabinofuranosylcytosine (cytarabine; ara-C) is the most active agent in myeloid leukemia. 5-Aza-2 ¶-deoxycytidine (DAC) is a cytosine analogue that inhibits DNA methylation and also has activity in myeloid leukemia.Therefore, we investigated combining these two drugs in human leukemia cell lines in vitro. Experimental Design: We initially examined the effects of ara-C and DAC on human leukemia cell lines HL60, ML-1, RAji, and Jurkat.We measured IC 50 of DAC and ara-C in these cell lines and cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 24 publications
7
99
0
Order By: Relevance
“…The chemosensitizing effect of demethylating agents has been previously described in several cancer cell lines (46)(47)(48). These studies showed that 5-aza and its analogues increase the apoptotic index of cancer cells exposed to various DNA-damaging agents, including irinotecan.…”
Section: Molecular Cancer Therapeuticsmentioning
confidence: 83%
“…The chemosensitizing effect of demethylating agents has been previously described in several cancer cell lines (46)(47)(48). These studies showed that 5-aza and its analogues increase the apoptotic index of cancer cells exposed to various DNA-damaging agents, including irinotecan.…”
Section: Molecular Cancer Therapeuticsmentioning
confidence: 83%
“…The antitumoral activity of decitabine was evaluated in vitro in several leukemic cell lines and solid tumors, where the 50% inhibitory concentration ranged from 10 nM to 10 mM. Concentrations of decitabine optimal to induce DNA hypomethylation reached a plateau above concentrations of 0.5 mM to 1 mM, whereas higher concentrations increased cytotoxicity [16][17][18][19].…”
Section: Nonclinical Aspects and Clinical Pharmacologymentioning
confidence: 99%
“…13,14 DNA-hypomethylating agents can sensitize resistant cancer cells to cytotoxic agents, [25][26][27][28] but this approach has been sparsely studied in clinical trials. Nonetheless, the use of an epigenetic modifier for chemosensitization appears to be safe, 29,30 and was reported to have restored cytarabine sensitivity to a cohort of younger patients with refractory acute lymphoblastic leukemia.…”
Section: Introductionmentioning
confidence: 99%